PERSEPSI MEREK DAN GAYA HIDUP PEMAKAI TAS “CHANNEL” (Studi Pada KonsumenOnline Shop) - Faiqotul Hima (Universitas muhammadiyah malang, 2016)
The purpose of this research is 1) To know and analyze the perception of consumers in the brand image (brand image) Channel bags and 2) To determine and analyze the lifestyle (lifestyle) Consumer Channel bag. The population in this study were all women in Malang who bought bags in the online shop, using judgmental sampling techniques can then be determined as many as 100 sample. The data analysis technique used in this research is the analysis of a range of scales.Based on the results of research and discussion that has been done, it can be concluded as follows: Consumer perception on brand image (brand image) bags Channel in the category brand catchy / recognizable, where the brand image (brand image) includes a unique logo, zipper logo chanel, stitch-patterned quilt (boxes), the price of comparable quality, have the serial number, made of calf leather and sheepskin, logo channel (2 c mesh), have the original card and rope chains of metal makes the consumer can easy to remember on Channel bag products. Perceptions on lifestyle (lifestyle) Consumer Channel bags can be obtained that the existence of the bag Channel can support activities, interests and opinions of consumers on the presence of products in the category Channel bag either. Lifestyle (lifestyle) consumer purse Channel can be seen that the respondents prefer to work outside the home, hobby of collecting bags, likes to shop, look for the latest fashion handbags. The consumer lifestyle can support recreational activities, family support on activities, knowledge, purchases of goods according to the needs and make the purchase because it becomes a habit.